Diversion In Children Criminal Justice System Through Restorative Justice - Yudi Hendarto; Umar Ma'ruf (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2018)
The formulation of the problem and the purpose of this study is to describe and analyze the diversion urgency in handling juvenile criminal cases, and to describe and analyze Perma No. 4 of 2014 on Diversion in criminal matters menyelesaian children through restorative justice approach. This research method using normative legal research methods dengn type of research is descriptive analytical. Based on the analysis result No. 4 of 2014 can be presented the following results, that Perma No. 4 of 2014 is needed in handling juvenile criminal cases. This is because during this time the condition of children who are in the coaching institutions, detention and permayarakatan far worse than a face appeared positive aspects of child development. Mixing children with adults in penitentiary have negative effects and its own psychological burden for the child, because he considered himself the same as adults with Perma No. 4 of 2014.Keywords: Diversion, Child Criminal Justice System, Restorative Justice